Guideline Checklist for Publishing Research Papers on Animal Experimentation and Comparative Medicine in China (2024 Edition) - Editorial Board of Laboratory Animal and Comparative Medicine (Shiyan dongwu yu bijiao yixue)
The standardization, transparency, and completeness of research papers in animal experimentation and comparative medicine research are crucial for ensuring the credibility, reproducibility, and clinical applicability of research findings. Internationally recognized guidelines, such as the ARRIVE guidelines, serve to standardize animal experimentation and reporting. In China, there is already a comprehensive framework of regulations and standards governing laboratory animal research. However, the practical guidance in these documents remains insufficient to effectively guide Chinese researchers in writing and publishing in vivo animal research papers. To address this gap, the Editorial Board of Laboratory Animals and Comparative Medicine has developed a checklist of publication standards tailored for Chinese scholars, informed by the ARRIVE 2.0 guidelines and Chinese regulations and standards. This checklist is applicable for authors to self-check during manuscript preparation and submission, for peer experts during the review process, for journal editors in pre-publication verification, and for readers to evaluate published works. It aims to effectively promote the standardization and high-quality development of laboratory animal and comparative medicine research in China.